2021
DOI: 10.21597/jist.824742
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Fruit Characteristics of Rosehips (Rosa canina L.) Grown in Bolu City Center

Abstract: Rosehip (Rosa spp.) is one of the most used non-wood forest products. It is an essential source of antioxidants and vitamin C besides having a wide range of uses in folk medicine and the marmalade industry. Therefore, for many years, researchers have made efforts to find the superior genotypes of this fruit. In previous studies, classical breeding methods were used in the evaluation of the data and more modernist approaches were given little attention. In this study, fruit characteristics and their relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…TPC showed strong relationships with TFC (r = 0.74 **) and DPPH (r = 0.84 **) (Table 4). Previously, Guler et al [9] used a number of rose hips and reported negative relationships between fruit SSC content and flesh weight, and positive correlation with FW and FFR. Cosmulescu et al [75] reported that there was strong relationship between antioxidant activity and total phenolic content in Rosa fruits.…”
Section: Principal Compenent Analysis (Pca)mentioning
confidence: 99%
See 2 more Smart Citations
“…TPC showed strong relationships with TFC (r = 0.74 **) and DPPH (r = 0.84 **) (Table 4). Previously, Guler et al [9] used a number of rose hips and reported negative relationships between fruit SSC content and flesh weight, and positive correlation with FW and FFR. Cosmulescu et al [75] reported that there was strong relationship between antioxidant activity and total phenolic content in Rosa fruits.…”
Section: Principal Compenent Analysis (Pca)mentioning
confidence: 99%
“…Apart from edible fruit, seeds, flowers etc. valued and used as food, medicine, fodder, fuel, agriculture, tools, fencing and ritualistic aspects, [7][8][9]. Over 30 Rosa species are found within Turkey's flora, Rosa canina and Rosa dumalis are the most common and recognized for their better fruit characteristics providing a rich source of Rosa products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pomological analyzes were carried out according to the mentioned literature (Ercisli, 1996;Gunes, 2010;Kazankaya et al, 2005;Najda and Buczwoska, 2013;Encu, 2015;Hatipoglu and Ak, 2021;Guler et al, 2021). After the harvest of rosehip/rose fruits that reached harvest maturity, the yields of the samples brought to the laboratory were determined, and the fruits of each taxon were counted and recorded.…”
Section: Pomological Analysismentioning
confidence: 99%
“…PCA was used to determine critical characters and to minimize the number of effective factors. Therefore, PCA has been used intensely by researchers to define critical characteristics of fruit species for the last decade (Mratinic, et al, 2011;Güler et al, 2021;Muradoğlu et al, 2021). In this study, PCA was conducted to characterize morphological characters of Turkish and foreign varieties.…”
Section: Differences In Morphological Characters Between Turkish and ...mentioning
confidence: 99%